Enhanced photoresponse of Cu2ZnSnS4 absorber thin films fabricated using multi-metallic stacked nanolayers. Issue 18 (18th April 2023) - Pandharkar, Subhash; Hase, Yogesh; Shah, Shruti; Doiphode, Vidya; Waghmare, Ashish; Punde, Ashvini; Shinde, Pratibha; Rahane, Swati; Bade, Bharat; Ladhane, Somnath; Prasad, Mohit; Patole, Shashikant P.; et al.
Abstract : Cu2 ZnSnS4 (CZTS) thin films have attracted considerable attention as potential candidates for photovoltaic absorber materials. Abstract : Cu2 ZnSnS4 (CZTS) thin films have attracted considerable attention as potential candidates for photovoltaic absorber materials. In a vacuum deposition technique, a sputtering stacked metallic layer followed by a thermal process for sulfur incorporation is used to obtain high-quality CZTS thin films. In this work, for fabricating CZTS thin films, we have done a 3LYS (3 layers), 6LYS, and 9LYS sequential deposition of Sn/ZnS/Cu metal stack ( via . metallic stacked nanolayer precursors) onto Mo-coated corning glass substrate via . RF-sputtering. The prepared thin films were sulfurized in a tubular furnace at 550 °C in a gas mixture of 5% H2 S + 95% Ar for 10 min. We further investigated the impact of the Sn/ZnS/Cu metal stacking layers on the quality of the thin film based on its response to light because metal inter-diffusion during sulfurization is unavoidable. The inter-diffusion of precursors is low in a 3-layer stack sample, limiting the fabricated film's performance. CZTS films with 6-layer and 9-layer stacks result in an improved photocurrent density of ∼38 μA cm −2 and ∼82 μA cm −2, respectively, compared to a 3-layer sample which has a photocurrent density of ∼19 μA cm −2 . This enhancement can be attributed to the 9-layer approach's superior inter-diffusion of metallic precursors and compact, smooth CZTS microstructure evolution.